Thermo-responsive shape memory polymer blends based on polylactic acid and polyethylene glycol - Pekdemir, Mustafa Ersin; Oner, Ecem Ozen; Kok, Mediha; Cherkezova, Aybolek (Polymer Soc Korea, 2024)
In this study, it is aimed to provide new functions to polymers by producing polymer blends. Two important biopolymers, PLA as the main matrix and PEG polymers were mixed in different ratios to produce shape memory (SM) PLA-PEG blend by solution method. The characteristic -C = O stretching vibration of PLA was observed as a strong signal in the ATR-FTIR spectra of the polymer blends. According to the heat flux versus temperature measurement results of PLA-PEG blends, characteristic peaks of each polymer were observed with increasing temperature. This result indicates that the polymer blends are immiscible. The thermal stability of the PLA-PEG blend was determined by thermogravimetric measurements and it was observed that the mass loss in the blend decreased with increasing PEG ratio. Since PEG and PLA are bicrystalline polymers, crystal structures of both polymers were found in X-ray measurements in the shape memory polymer blends produced. Finally, it was found that the produced PLA-PEG blend showed shape memory property and the blend could return to its original shape in as short as 8 sec.
Keywords: Poly Lactic acid; Poly ethylene glycol; Blend; Thermo-responsive; Shape memory